WTD Attenuating Rheumatoid Arthritis via Suppressing Angiogenesis and Modulating the PI3K/AKT/mTOR/HIF-1α Pathway - Ba, Xin; Huang, Ying; Shen, Pan; Huang, Yao; Wang, Hui; Han, Liang; Lin, Wei Ji; Yan, Hui Jia; Xu, Li Jun; Qin, Kai; Chen, Zhe; Tu, Sheng Hao (Frontiers in Pharmacology, 2021)
Background: Wutou Decoction (WTD), as a classic prescription, has been generally used to treat rheumatoid arthritis (RA) for two thousand years in China. However, it is rarely reported the potential protective effect of WTD on rheumatoid arthritis and its possible mechanism. Purpose：The study aim is to explore the potential protective effect and possible mechanism of WTD on RA. Methods: Collagen-induced arthritis (CIA) rat was constructed to assess the therapeutic effect of WTD on it. Histopathological staining, immunofluorescence, and western blot of synovial sections were conducted to detect the effect of WTD anti- angiogenesis. Then, cell viability assay, flow cytometry, Scratch healing assay, and invasion assay were conducted to explore the effect of WTD on human fibroblast-like synoviocyte (FLS) line (MH7A) proliferation apoptosis, migration, invasion in vitro. The ability of WTD inducing blood vessel formation after MH7A and human umbilical vein endothelial cell line (HUVEC) co-cultures with WTD intervention was detected by tube formation. The mechanisms of WTD were screened by network pharmacology and confirmed by experiments in vivo and in vitro. Results：WTD ameliorated the symptoms and synovial pannus hyperplasia of CIA rats. Interfering with WTD, we found that WTD could inhibit MH7A proliferation, migration, invasion, and promote MH7A apoptosis. WTD could inhibit MH7A expression of pro-angiogenesis factors, including VEGF and ANGI, to induce HUVEC tube formation. Furthermore, the PI3K-AKT-mTOR-HIF-1α pathway is enriched as a potential target of WTD treatment RA through network pharmacological enrichment analysis. Finally, it was confirmed that WTD inhibits the angiogenesis of RA by interrupting the PI3K-AKT-mTOR-HIF-1α pathway in vitro and in vivo experiments. Conclusion：WTD can inhibit synovial hyperplasia and angiogenesis, presumably by inhibiting migration and invasion of MH7A, and blocking the production of pro-angiogenesis effectors of MH7A. The possible underlying mechanism of WTD ameliorating angiogenesis of RA is the PI3K-AKT-mTOR-HIF-1α pathway.